What Is the Reference? An Examination of Alternatives to the Reference Sources Used in IES TM-30-15. Issue 2 (3rd April 2017) - Royer, Michael P.
ABSTRACT: This article documents the role of the reference illuminant in the IES TM-30-15 method for evaluating color rendition. TM-30-15 relies on a relative reference scheme; that is, the reference illuminant and test source always have the same correlated color temperature (CCT). The reference illuminant is a Planckian radiator, model of daylight, or combination of those two, depending on the exact CCT of the test source. Three alternative reference schemes were considered: (1) either using all Planckian radiators or all daylight models, while maintaining the CCT match of the test and reference; (2) using only one of 10 possible illuminants (Planckian, daylight, or equal energy), regardless of the CCT of the test source; (3) using an off-Planckian reference illuminant (that is, a source with a negative D uv ). No reference scheme is inherently superior to another, with differences in metric values largely a result of small differences in gamut shape for the reference alternatives. Though using any of the alternative schemes is more reasonable in the TM-30-15 evaluation framework than it was with the CIE Test Color Method, the differences still ultimately manifest only as changes in interpretation of the results. Reference illuminants are employed in TM-30 to provide a familiar point of comparison, not to establish an ideal source.